Partial Deletion of Tie2 Affects Microvascular Endothelial Responses to Critical Illness in A Vascular Bed and Organ-Specific Way. Issue 6 (June 2019) - Jongman, Rianne M.; Zwiers, Peter J.; van de Sluis, Bart; van der Laan, Marleen; Moser, Jill; Zijlstra, Jan G.; Dekker, Daphne; Huijkman, Nicolette; Moorlag, Henk E.; Popa, Eliane R.; Molema, Grietje; van Meurs, Matijs
Abstract : ABSTRACT: Tyrosine kinase receptor (Tie2) is mainly expressed by endothelial cells. In animal models mimicking critical illness, Tie2 levels in organs are temporarily reduced. Functional consequences of these reduced Tie2 levels on microvascular endothelial behavior are unknown. We investigated the effect of partial deletion of Tie2 on the inflammatory status of endothelial cells in different organs. Newly generated heterozygous Tie2 knockout mice (exon 9 deletion, ΔE9/Tie2 +/− ) exhibiting 50% reduction in Tie2 mRNA and protein, and wild-type littermate controls (Tie2 +/+ ), were subjected to hemorrhagic shock and resuscitation (HS + R), or challenged with i.p. lipopolysaccharide (LPS). Kidney, liver, lung, heart, brain, and intestine were analyzed for mRNA levels of adhesion molecules E-selectin, vascular cell adhesion molecule 1 (VCAM-1), and intercellular cell adhesion molecule 1 (ICAM-1), and CD45. Exposure to HS + R did not result in different expression responses of these molecules between organs from Tie2 +/− or Tie2 +/+ mice and sham-operated mice. In contrast, the LPS-induced mRNA expression levels of E-selectin, VCAM-1, and ICAM-1, and CD45 in organs were attenuated in Tie2 +/− mice when compared with Tie2 +/+ mice in kidney and liver, but not in the other organs studied. Furthermore, reduced expression of E-selectin and VCAM-1 protein, and reduced influx of CD45 + cells upon LPS exposure, was visible in a microvascular bed-specific pattern in kidney and liver of Tie2 +/− mice compared with controls. In contrast to the hypothesis that a disbalance in the Ang/Tie2 system leads to increased microvascular inflammation, heterozygous deletion of Tie2 is associated with an organ-restricted, microvascular bed-specific attenuation of endothelial inflammatory response to LPS. Abstract : Supplemental Digital Content is available in the text